Factors influencing customer patronage behavior towards Kedai Rakyat 1 Malaysia (KR1M) / Ahmad Afiq Zakri, Aida Suraya Abdul Rahim & Nurul Izzati Idrus - Zakri, Ahmad afiq; Abdul Rahim, Aida Suraya; Idrus, Nurul Izzati (2014)
The research explores customer patronage behavior of visitors who frequent the Kedai Rakyat 1 Malaysia (KR1M) with the aim of understanding who the main customers are and why they frequent KR1M. It is postulated that price perception, convenience, service quality, variety of assortment and sales and promotion are variables influencing customer patronage of retail outlets. By using the descriptive method of study based on the survey approach, questionnaires were distributed to 120 respondents. The mall intercept method was utilized as a means of collecting data. Data accumulated was analyzed using descriptive analysis together with correlation and regression analyses to answer the stated research objectives. The outcome of the study found that convenience was the most influencing variable on customer patronage. Although all the variables showed positive correlation with customer patronage, convenience was found to be the main reason that customers frequent KR1M. The recommendation outlined in the study suggested that market penetration would be the best alternative to enhance market growth of KR1M as the present customers appeared to be in line with the target market of KR1M. This strategy was also aligned with KR1M's present Corporate Social Responsibility (CSR) initiative of serving the needs of the urban poor and to ensure that their welfare would be addressed appropriately.